Long-lasting improvements in episodic memory among subjects with mild cognitive impairment who received transcranial direct current stimulation combined with cognitive treatment and telerehabilitation: a multicentre, randomized, active-controlled study - Manenti, Rosa; Baglio, Francesca; Pagnoni, Ilaria; Gobbi, Elena; Campana, Elena; Alaimo, Cristina; Rossetto, Federica; Di Tella, Sonia; Pagliari, Chiara; Geviti, Andrea; Bonfiglio, Natale Salvatore; Calabrò, Rocco Salvatore; et al. (Frontiers in aging neuroscience, 2024)
In recent years, an increasing number of studies have examined the potential efficacy of cognitive training procedures in individuals with normal ageing and mild cognitive impairment (MCI). The aims of this study were to (i) evaluate the efficacy of the cognitive Virtual Reality Rehabilitation System (VRRS) combined with anodal transcranial direct current stimulation (tDCS) applied to the left dorsolateral prefrontal cortex compared to placebo tDCS stimulation combined with VRRS and (ii) to determine how to prolong the beneficial effects of the treatment. A total of 109 subjects with MCI were assigned to 1 of 5 study groups in a randomized controlled trial design: (a) face-to-face (FTF) VRRS during anodal tDCS followed by cognitive telerehabilitation (TR) (clinic-atDCS-VRRS+Tele@H-VRRS); (b) FTF VRRS during placebo tDCS followed by TR (clinic-ptDCS-VRRS+Tele@H-VRRS); (c) FTF VRRS followed by cognitive TR (clinic-VRRS+Tele@H-VRRS); (d) FTF VRRS followed by at-home unstructured cognitive stimulation (clinic-VRRS+@H-UCS); and (e) FTF cognitive treatment as usual (clinic-TAU). An improvement in episodic memory was observed after the end of clinic-atDCS-VRRS ( < 0.001). We found no enhancement in episodic memory after clinic-ptDCS-VRRS or after clinic-TAU.Moreover, the combined treatment led to prolonged beneficial effects (clinic-atDCS-VRRS+Tele@H-VRRS vs. clinic-ptDCS-VRRS+Tele@H-VRRS: = 0.047; clinic-atDCS-VRRS+Tele@H-VRRS vs. clinic-VRRS+Tele@H-VRRS: = 0.06). The present study provides preliminary evidence supporting the use of individualized VRRS combined with anodal tDCS and cognitive telerehabilitation for cognitive rehabilitation. https://clinicaltrials.gov/study/NCT03486704?term=NCT03486704&rank=1, NCT03486704.